Design and Development of a Web-Based Informed Consent Information System to Improve the Efficiency and Legal Compliance of Healthcare Administrative Services - Syifa Putri Carissa Candraningtyas; Yuyun Yunengsih; Rina Kurniawati (Greenation Research & Yayasan Global Resarch National, 2026)
This study aims to design a web-based Informed Consent Information System to improve administrative efficiency and support the legality of healthcare services. The research method used is the Waterfall method, encompassing the stages of requirements analysis, system design, implementation, testing, and maintenance. The resulting system is a web-based application featuring patient data management, physician data management, medical procedure data, electronic medical procedure consent forms, electronic signatures, as well as the printing of Informed Consent documents and reports. This system was designed as a solution to the problems identified through observations at Tk. II Dustira Hospital, where Informed Consent documents were still managed manually, resulting in inefficiencies in the storage, archiving, and retrieval processes. The system has proven capable of simplifying the management of medical procedure consent documents, improving the administrative efficiency of healthcare services, and supporting digital, structured, and easily accessible document storage whenever needed.